2017
DOI: 10.53369/kddl1000
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Corporate Governance on the Financial Distress: Evidence from Pakistani Listed Companies

Abstract: This study intends to assess how corporate governance affects the financial distress in non-financial listed companies in Pakistan. Sample of 53 companies was obtained from non-financial institutes listed in Pakistani stock exchange. Regression analysis is used to estimate the impact of explanatory variables including size of board, composition of board, audit committee independence and duality of CEO on the financial distress. The findings show that size of board, composition of board and CEO duality has a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
1
1
0
2
Order By: Relevance
“…Therefore, our study found no impact of audit committee independence on the financial distress of a company. The result of the study is consistent with that of Jamal and Shah (2017).…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, our study found no impact of audit committee independence on the financial distress of a company. The result of the study is consistent with that of Jamal and Shah (2017).…”
Section: Discussionsupporting
confidence: 91%
“…Many studies have been conducted in the local context to examine the impact of effective governance mechanisms on the likelihood of FD and have concluded that an efficient governance structure not only improves a firm financial performance but also protects it from FD (Jamal and Shah, 2017;Taj et al, 2017;Udin et al, 2017;Khurshid et al, 2018;Khalid et al, 2020;Farooq et al, 2020). Management is expected to use CSR activities to align the interests of various stakeholder groups in an effective governance structure, thereby indirectly protecting the firm from distress.…”
Section: Corporate Social Responsibility Financial Distress and Corpo...mentioning
confidence: 99%
“…Penelitian sebelumnya menemukan independent commissioners berefek negatif dengan financial distress yang dihadapi perusahaan (Fathonah 2016;Pramudena 2017;Hanani and Dharmastuti 2015;Indarti, Widiatmoko, and Pamungkas 2021). Hasil pengujian sebelumnya membuktikan board size berpengaruh positif terhadap financial distress karena jika perusahaan memiliki dewan direksi yang besar, resiko financial distress menjadi tinggi (Younas et al 2021;Guizani and Abdalkrim 2023;Jamal and Shah 2017). Ini menyiratkan bahwa dengan memiliki lebih banyak direktur di dewan, itu dapat menunda proses pengambilan keputusan.…”
Section: Pendahuluanunclassified
“…Semakin banyak pihak yang independen dalam komite, maka tidak akan dapat menciptakan pengawasan lebih optimal. Hasil ini serupa dengan temuan sebelumnya yang menyatakan audit committee independence tidak berpengaruh terhadap financial distress (Gebrayel et al 2018;Jamal and Shah 2017;Ragab and Saleh 2022). Akan tetapi, penelitian ini berbeda dengan hasil temuan lain yang membuktikan audit committee independence berpengaruh terhadap financial distress (Farooq, Noor, and Fatima 2020;Ashraf, Félix, and Serrasqueiro 2021;Yakubu, Abdullahi, and Ibrahim 2020;Khalid et al 2020;Luqman et al 2018).…”
Section: Hasil Uji Tunclassified